Implications of elevated troponin on time-to-surgery in non-ST elevation myocardial infarction (NIHR Health Informatics Collaborative: TROP-CABG study) - Benedetto, U; Sinha, S; Mulla, A; Glampson, B; Davies, J; Panoulas, V; Gautama, S; Papadimitriou, D; Woods, K; Elliott, P; Hemingway, H; Williams, B; et al. (Elsevier, 2022)
Background The optimal timing of coronary artery bypass grafting (CABG) in patients with non-ST elevation myocardial infarction (NSTEMI) and the utility of pre-operative troponin levels in decision-making remains unclear. We investigated (a) the association between peak pre-operative troponin and survival post-CABG in a large cohort of NSTEMI patients and (b) the interaction between troponin and time-to-surgery. Methods and results Our cohort consisted of 1746 patients (1684 NSTEMI; 62 unstable angina) (mean age 69 ± 11 years,21% female) with recorded troponins that had CABG at five United Kingdom centers between 2010 and 2017. Time-segmented Cox regression was used to investigate the interaction of peak troponin and time-to-surgery on early (within 30 days) and late (beyond 30 days) survival. Average interval from peak troponin to surgery was 9 ± 15 days, with 1466 (84.0%) patients having CABG during the same admission. Sixty patients died within 30-days and another 211 died after a mean follow-up of 4 ± 2 years (30-day survival 0.97 ± 0.004 and 5-year survival 0.83 ± 0.01). Peak troponin was a strong predictor of early survival (adjusted P = 0.002) with a significant interaction with time-to-surgery (P interaction = 0.007). For peak troponin levels <100 times the upper limit of normal, there was no improvement in early survival with longer time-to-surgery. However, in patients with higher troponins, early survival increased progressively with a longer time-to-surgery, till day 10. Peak troponin did not influence survival beyond 30 days (adjusted P = 0.64). Conclusions Peak troponin in NSTEMI patients undergoing CABG was a significant predictor of early mortality, strongly influenced the time-to-surgery and may prove to be a clinically useful biomarker in the management of these patients.